Dark exciton preparation in a quantum dot by a longitudinal light field tuned to higher exciton states - Holtkemper, M. (2021)
Several important proposals to use semiconductor quantum dots in quantum information technology rely on the control of the dark exciton ground states, such as dark exciton based qubits with a microsecond lifetime. In this paper, we present an efficient way to occupy the dark exciton ground state by a single short laser pulse. The scheme is based on an optical excitation with a longitudinal field component featured by, e.g., radially polarized beams or certain Laguerre-Gauss or Bessel beams. Utilizing this component, we show within a configuration interaction approach that high-energy exciton states composed of light-hole excitons and higher dark heavy-hole excitons can be addressed. When the higher exciton relaxes, a dark exciton in its ground state is created.